Imaging profile of the ear in hearing loss patients in Hospital Universiti Sains Malaysia - Japar@Jaafar, Rohaizam (2015)
Introduction: Hearing impairment is a major disability. The otologic assessments together with high-resolution CT images were able to obtain precise diagnostic profile of ear malformations. These details are essential for further management of patients. Objective: This study was conducted to investigate the detailed anatomical profile of the ears in hearing loss patient in Hospital Universiti Sains Malaysia by highresolution CT scan of the temporal bone. Methodology: This was a cross-sectional study of high resolution CT scans of temporal bone from 1st January 2008 to 31st May 2014 in HUSM. The study sample consisted of all patients with hearing loss who had undergone HRCT in HUSM and fulfilled the study criteria. Results: In this study, which consisted of 55 patients, 40% of patients showed some form of abnormality on the HRCT temporal bone with 36.4% with outer ear abnormality, 9.0% had middle ear abnormality, 40.1% noted to have inner ear abnormality and 13.6% with multiple areas of abnormality. In term of laterality, 54.5% were observed to have bilateral diseases, 27.3% on right ear and the remaining 18.2% had it on the left ear. The mean vestibular aqueduct diameter was 0.08 ± 0.09 cm (R) and 0.06 ± 0.04 cm (L), lateral semicircular canal diameter 0.10 ± 0.03 cm (R) and 0.10 ± 0.02 cm (L), vestibule diameter 0.30 ± 0.06 cm (R) and 0.31 ± 0.05 cm (L), bone width between the lateral vestibular wall and the inner wall of the lateral semicircular canal diameter 0.35 ± 0.07 cm (R) and (L) and internal acoustic meatus diameter 0.40 ± 0.08 cm (R) and 0.41 ± 0.08 cm (L). Patients with external ear abnormality were observed to have normal to severe hearing loss, patients with middle ear abnormality had mild to severe hearing loss and patients with inner ear abnormality had normal to profound hearing loss. The most common inner ear abnormalities in this study were enlarged vestibular aqueduct and cochlear ossifications. Conclusion: This study showed that HRCT temporal bone could detect ear abnormality up to 40% of patients with hearing loss and most common abnormality would be enlarged vestibular aqueduct and cochlear ossification. The severity of hearing loss was higher in patients with inner ear abnormality.